The Role of the Manarul Ilmi Mosque in Strengthening Religious Moderation and Character Education for ITS Surabaya Muslim Students - Mahfud, Choirul; Ratna Rintaningrum; Moh. Saifulloh; Wahyuddin Wahyuddin; Zainul Muhibbin; Aurelius Ratu (Jurnal Pendidikan Agama Islam Al-Thariqah, 2024)
Character education development is an unfinished process. The Sepuluh Nopember Institute of Technology (ITS) Surabaya is one of the favorite state campuses which also pays attention to scientific and Islamic development through developing the role of the Manarul Ilmi campus mosque. ITS Surabaya realizes that developing character education is a shared responsibility. In this context, this research is qualitative in nature with a descriptive analytical approach and uses documentary methods supported by interviews. The general aim of this research is to find out what and how to develop Muslim character education and the educational role of the Manarul Ilmi mosque at ITS Surabaya? What are the challenges, obstacles and solutions in developing character education and religious moderation for Muslim students through the Manarul Ilmi ITS Surabaya mosque? The research results show that the educational role of the Manarul Ilmi mosque at ITS Surabaya is very significant in developing character education and religious moderation for intelligent, trustworthy and creative Muslim students through various activities, training, discussion forums, routine studies and program synergies